2010
DOI: 10.1093/neuonc/noq082
|View full text |Cite
|
Sign up to set email alerts
|

Glioma cancer stem cells induce immunosuppressive macrophages/microglia

Abstract: Macrophages (MΦs)/microglia that constitute the dominant tumor-infiltrating immune cells in glioblastoma are recruited by tumor-secreted factors and are induced to become immunosuppressive and tumor supportive (M2). Glioma cancer stem cells (gCSCs) have been shown to suppress adaptive immunity, but their role in innate immunity with respect to the recruitment and polarization of MΦs/microglia is unknown. The innate immunosuppressive properties of the gCSCs were characterized based on elaborated MΦ inhibitory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
502
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 558 publications
(517 citation statements)
references
References 66 publications
10
502
1
4
Order By: Relevance
“…This change in the immune response of microglia is in agreement with the pathologic results in vivo [33,34]. This phenomenon might be induced by glioma stem cells, which are considered to contribute to the conversion of microglia from classically activated M1 to immunosuppressive M2 phenotypes, which impede the phagocytic ability of microglia [35].…”
Section: Discussionsupporting
confidence: 87%
“…This change in the immune response of microglia is in agreement with the pathologic results in vivo [33,34]. This phenomenon might be induced by glioma stem cells, which are considered to contribute to the conversion of microglia from classically activated M1 to immunosuppressive M2 phenotypes, which impede the phagocytic ability of microglia [35].…”
Section: Discussionsupporting
confidence: 87%
“…A critical therapeutic advantage in using cytotoxins via CED is that they cause death of targeted cells (70). Even though the GBM tumor environment is highly immunosuppressive (98,99) and patients with GBM are immunosuppressed (100, 101), a large number of killed tumor cells provides a "danger signal" and evokes effective antitumor immune responses. Our published (41) and unpublished observations suggested, and another study demonstrated directly (102), the existence of effective immune responses in preclinical studies with cytotoxic proteins.…”
Section: Promising Treatment Bypassing the Bbbmentioning
confidence: 99%
“…However, studies have shown that cancer stem cells have the ability to evade the immune system (Schneider et al, 2011;Wei et al, 2010;Wu et al, 2010). Therefore, new cancer treatment therapy to target cancer stem cells by enhancing the immune system is important and necessary.…”
Section: Cancersmentioning
confidence: 99%